Sustainable socialized housing urban food production through hydroponic farming within a public housing development - Cachola, Sofia Ysabelle T.; de Leon, Ruby Teresa (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
With the Philippines’ shortcomings to address the growing statistics for hunger and homelessness within a virus-struck country, marginalized communities are made even more susceptible to the inaccessibility to proper housing, as well as sustainable and inexpensive sources for food and nutrition. These long-standing issues were focused on to highlight the declining socio-economic profile of the urban poor and to shed light on what can potentially be a more sustainable model for socialized housing within the country’s urban environments. Socialized housing which integrates hydroponic, vertical farming to the development offers solutions to both problems by generating a multi-purpose development that not only provides the chosen impoverished community with shelter and security, but also maintains that security through a feasible measure to cultivate a viable supply of vegetable produce within the Philippines’ urban context as well as pose possibilities for the means in which inhabitants could engage in productive recreation. This thesis explores the design issues and architectural goals in sustainable socialized housing and urban farming through qualitative research regarding impoverished communities, as well as quantitative, second data analysis of topics regarding socialized housing, food security, and vertical farming. These methods along with the careful consideration of prevailing codes, standards and conditions are aimed to formulate a more holistic and expedient architectural design solution for a more sustainable model for socialized housing.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Hydroponics; Urban agriculture; Urban poor; Housing